An experimental and theoretical study of the photoelectron spectra of cis-dichloroethene: Valence shell vertical ionization and vibronic coupling in the low-lying cationic states. - Trofimov, Alexander; Gromov, Evgeniy; Köppel, Horst (The journal of chemical physics, 2018)
The valence shell photoelectron spectrum of cis-dichloroethene has been studied both experimentally and theoretically. Photoelectron spectra have been recorded with horizontally and vertically plane polarized synchrotron radiation, thereby allowing the anisotropy parameters, characterizing the angular distributions, to be determined. The third-order algebraic-diagrammatic construction approximation scheme for the one-particle Green's function has been employed to compute the complete valence shell ionization spectrum. In addition, the vertical ionization energies have been calculated using the outer valence Green's function (OVGF) method and the equation-of-motion coupled-cluster, with single and double substitutions for calculating ionization potentials (EOM-IP-CCSD) model. The theoretical results have enabled assignments to be proposed for most of the structure observed in the experimental spectra, including the inner-valence regions dominated by satellite states. The linear vibronic coupling model has been employed to study the vibrational structure of the lowest photoelectron bands, using parameters obtained from ab initio calculations. The ground state optimized geometries and vibrational frequencies have been computed at the level of the second-order Møller-Plesset perturbation theory, and the dependence of the ionization energies on the nuclear configuration has been evaluated using the OVGF method. While the adiabatic approximation holds for the X̃2B1 state photoelectron band, the Ã2B2, B̃2A1, and C̃2A2 states interact vibronically and form a complex photoelectron band system with four distinct maxima. The D̃2B1 and Ẽ2B2 states also interact vibronically with each other. The potential energy surface of the D̃2B1 state is predicted to have a double-minimum shape with respect to the out-of-plane a2 deformations of the molecular structure. The single photoelectron band resulting from this interaction is characterized by a highly irregular structure, reflecting the non-adiabatic nuclear dynamics occurring on the two coupled potential energy surfaces forming a conical intersection close to the minimum of the Ẽ2B2 state.
Gesehen am 23.05.2019